Practices of EFL Teachers on Metacognition: A Case Study of a Saudi University - EJAZ, Ahmed (University Malaysia Sarawak, 2025)
study examined teachers' metacognitive processes in non-native English contexts. Data collected through classroom observations, semi-structured interviews, and stimulated recall interviews from the teachers at a Saudi university. Classroom observations conducted to capture authentic teaching practices, while semi-structured interviews provided insights into teachers' beliefs and experiences. Stimulated recall interviews allowed for a deeper exploration of specific teaching moments. Qualitative data analysis techniques, including open, axial, and selective coding, employed to identify patterns in teacher behavior and thought processes. Atlas.ti9 used to facilitate data management and analysis. Findings indicate that teachers' metacognitive awareness significantly influences their teaching practices and student outcomes. Participants demonstrated a range of metacognitive strategies, such as planning, monitoring, evaluation, and regulation. These strategies were evident in various classroom activities, including lesson planning, instructional delivery, and student feedback. The study highlights the importance of fostering metacognitive development among teachers to enhance overall teaching effectiveness. Keywords: Practices, metacognition, metacognitive strategies, observation, semi-structured interviews